2020
DOI: 10.3889/oamjms.2020.5013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Characteristics of Patients with COVID-19 Who Died in Modarres Hospital

Abstract: BACKGROUND: Novel coronavirus disease (COVID-19) is caused by severe acute respiratory syndrome-CoV2 as a century concern affecting public health. AIM: This study aimed to find the clinical and demographic characteristics of the patients died following COVID-19 development at Modarres Hospital, Tehran, Iran. METHODS: In this descriptive-analytical cross-sectional study, 62 patients died following COVID-19 were studied in terms of age, gender, body mass index, comorbidity, symptoms, liver profile, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…27 In a study by Besharat et al, the results showed that 71% of patients were male and the mean age was 67.62 years with symptoms lasting 6.24 days. 28 This study was consistent with our results regarding the duration of the symptoms that may be related to the genetics (level of ACE2 receptors) of the same population. 29 Like our study, Besharat et al reported that fever, cough, and shortness of breath were dominant symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…27 In a study by Besharat et al, the results showed that 71% of patients were male and the mean age was 67.62 years with symptoms lasting 6.24 days. 28 This study was consistent with our results regarding the duration of the symptoms that may be related to the genetics (level of ACE2 receptors) of the same population. 29 Like our study, Besharat et al reported that fever, cough, and shortness of breath were dominant symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…29 Like our study, Besharat et al reported that fever, cough, and shortness of breath were dominant symptoms. 28 In conclusion, according to the results, the mean time from onset of symptoms to hospitalization, isolation, and discharge were similar in women and men. ICU admission was about four times higher in men than women and the most common comorbidity in women and men was cardiovascular disease and diabetes.…”
Section: Discussionmentioning
confidence: 64%
“…The summary of characteristics extracted from studies is presented in Table 1. From 22 included studies, 9 were cohort (17,(19)(20)(21)(23)(24)(25)33,36), 8 were cross-sectional (26,(30)(31)(32)34,35,37,38), one was case-control (28), and 4 were trials (18,22,27,29). Nineteen studies had completed peer-review processes and were published from June to November 2020; while three studies (21,24,32) were not granted publication and peer-review at the time of inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, patients were specifically from intensive care unit (ICU) (19,30,31). Two studies enrolled a population of kidney transplant recipients (37,38), one only deceased patients (34), and one patients who underwent concurrent cardiac surgery (36). The funnel plot to evaluate publication bias is demonstrated in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…The COVID-19 has not been previously found in humans; up to now, no specific effective antiviral therapies have been identified for it. Besides, the virus infection diagnosis is difficult and crucial in most cases [3,4].…”
Section: Introductionmentioning
confidence: 99%